Upper and Middle Neosho Watersheds Assessment: Preliminary Report - Nejadhashemi, A. P.; Perkins, S.A.; Smith, C.M.; Mankin, K.R.; Wilson, R.M.; Brown, S.P.; Leatherman, J.C. (My University, 2009)
A preliminary assessment of the upper and middle Neosho Watershed in southeast Kansas.
EP135_2009-02
Keywords: EP135; Environment and Natural Resources; EP